Development of a multi-zone adiabatic reactor optimization framework for oxidative coupling of methane - Murtaza Ali Khan (22804274) (2025)
Managing heat is a major challenge for oxidative coupling of methane (OCM) because of its high exothermicity. While recent innovations have mainly focused on reactor design, most studies assume isothermal operation, which is often impractical for scale-up. Adiabatic operation better reflects industrial conditions but remains underexplored. Additionally, little attention has been given to distributing O2 along the reactor or using interstage cooling to smooth temperature variations inside the OCM reactor and improve performance. In this work, we address those gaps by optimizing a multi-zone reactor design with distribution feeding of O2. Using Simulated Annealing, we model up to 30 reactor zones, each treated as a fixed-bed, one-dimensional and pseudo-homogeneous system. Our results show that distributing oxygen across multiple zones with interstage cooling increases the C2 yield by almost 8 times, from 5.7% in a single zone to 46.5 % across 30 zones, achieving smoother temperature profiles without changing the catalyst. Other Information Published in: Chemical Engineering Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ces.2025.123040